Fabrication and characterization of antioxidant biodegradable plastic from mangrove starch, chitosan, and clove essential oil - Syaubari, Syaubari; Dawood, Jimmy; Zaki, Muhammad; Bachtiar, Dandi (Jurnal Polimesin, 2025)
The development of  biodegradable plastics offers a  sustainable alternative to conventional ones, reducing environmental impact. This research is the fabrication and characterization of biodegradable plastic films derived from large-leafed mangrove (Bruguiera gymnorrhiza) starch, chitosan, and clove essential oil (CEO)  as  an  antioxidant  additive.  Glycerol  was  used  as  a plasticizer, while carboxymethyl cellulose (CMC) and carrageenan were incorporated as thickeners. The effects of glycerol (2.7–9 ml), chitosan (4– 6% m/m), and CEO (0–8% m/m) concentrations on mechanical properties, morphology, and biodegradability were examined. Fourier-transform infrared (FTIR) spectroscopy confirmed the successful incorporation of chitosan and CEO. Scanning electron microscopy (SEM) revealed surface roughness and cavities due to incomplete chitosan dissolution. The optimized formulation (3% starch, 5 ml glycerol, 5% chitosan, and 5% CEO) exhibited superior mechanical properties, with a tensile strength of 710.98 MPa, Young’s modulus of 582.65 MPa, and elongation at break of 121.4%. Soil burial tests demonstrated complete degradation within 14 days. These findings highlight the potential of mangrove starch-based bioplastics for food packaging and eco-friendly applications.